In vivo photoinduced [4 + 2] dimerization of a neo-clerodane diterpene in Baccharis flabellata. ROS and RNS scavenging abilities - Funes, Matías Daniel (2018)
Secondary metabolites play a major role in the adaptation of plants to the environment. Furan neo-clerodane diterpenes are characteristic secondary metabolites in Baccharis flabellata Hook. & Arn. var. flabellata. One of the main compounds is the diene ent-15,16-epoxy-19-hydroxy-1,3,13(16),14-clerodatetraen-18-oic acid (DAC). In this work a new dimeric compound (DACD) has been isolated and identified by NMR and MS techniques. The presence of other minor dimers was also observed in the same plant methanolic extracts. Assuming that they may be the products of [4 + 2] condensation of two monomeric moieties, the formation of adducts by photochemical dimerization was checked by inducing the in vitro [4 + 2] cycloaddition of DAC. Moreover, the DAC and DACD accumulation rates in aerial parts of B. flabellata specimens were analyzed monthly during a complete phenological cycle. The accumulation of monomer depends on the plant phonological stage; meanwhile the dimer proportion arises in detriment of the monomer as the solar UV radiation increases. Since plants exposed to strong UV intensities produce radical species, the scavenger properties of these compounds toward reactive nitrogen species (RNS), and reactive oxygen species (ROS), were analyzed. Albeit DAC and DACD show significant superoxide radical scavenger activities, the monomer proved to be more effective than the dimer toward ROS, while DACD was an excellent RNS scavenger.